Preparation of high solid content oxidized starch by acid pretreatment–H2O2 oxidation and its performance as the ligand in zirconium tanning. (January 2022) - Wang, Jiaying; Yu, Yue; Yue, Wang; Feng, Yuhe; Wang, Ya-nan; Shi, Bi
Abstract: Highly-oxidized starch (HOS) is an excellent ligand for zirconium tanning in leather making. However, oxidation reaction can only be undertaken in diluted solution due to the high viscosity of starch, which leads to high oxidant consumption and low solid content of HOS, and therefore greatly limits its industrial application. Starch was predegraded by using HCl followed by H2 O2 oxidation for preparing a practical oxidized starch (OST) ligand with high solid content. HCl (5%) remarkably reduced the viscosity of starch and simplified the subsequent oxidation, resulting in a decrease in H2 O2 dosage from 60% to 40% and an increase in solid content from 10% to 38%. HCl broke the α-(1–4) glycosidic bond between glucose units, and H2 O2 oxidation led to the generation of abundant carboxyl groups in OST. The OST with moderate molecular weight ( Mw 5609 g/mol) and carboxyl content (6.48 mmol/g) made the tanning performance of OST–Zr comparable to those of HOS–Zr and chrome tanning agents. Therefore, this work gives new insights into the crop-polysaccharides based ligands application and exhibits huge potential for promoting industrial applications of zirconium tanning. Graphical abstract: Image 1 Highlights: Starch was predegraded by using HCl to reduce its viscosity and simplify oxidation. Predegraded starch was oxidized by using H2 O2 to introduce carboxyl group. H2 O2 dosage reduced from 60% to 40%, and solid content increased from 10% to 38%. Oxidized starch promoted the penetration and fixation of zirconium salt in leather. Starch-based ligand with high solid content greatly improved its practicability.